Current Prospectives of Hormone Therapy in Breast Cancer Treatment - Udaysimha, Vaibhavi; Prateeksha G,; Arpitha R S,; Hiremath, Lingayya (Journal of Mines, Metals and Fuels, 2023)
Breast cancer, being a heterogeneous disease, includes an increased proliferation of breast cells, symptoms of which includelump in the breast, bloody discharge from the nipple area, and changes in the shape or texture of the nipple or breast. The types of breast cancer mainly encompass adenocarcinomas and angiosarcoma. The treatment of this disease depends on the stage. It incorporates local therapy like surgery and radiotherapy and systemic therapy like chemotherapy, hormone therapy, and biological therapy. Oestrogen and progesterone stimulate breast cells to grow and multiply. Hormone therapy is usually provided to patients whose tumors are hormone receptor-positive, meaning the hormones bind extensively to the surface receptors of the tumor cells and cause increased multiplication. Chemotherapy is usually more effective for patients with a high recurrence score, whereas hormone therapy is best used for low recurrence scores. Hormone therapy blocks the interaction of hormones with their specific receptors to prevent the development of tumors and is used in both adjuvant and metastatic cancers. In this our study focused on the course of action to treat breast cancer with hormone therapy is Selective estrogen receptor modulators such as Tamoxifen and raloxifene and other parameters with support of Nano-materials applications in preventing breast cancer.